Psychosocial and clinical burden of thalassaemia intermedia and its implications for prenatal diagnosis. Issue 5 (May 1995) - Ratip, S; Skuse, D; Porter, J; Wonke, B; Yardumian, A; Modell, B
Abstract : Twenty eight patients with thalassaemia intermedia and their parents were interviewed using specifically designed questionnaires to evaluate psychosocial burden. Hospital notes were analysed for clinical burden. A wide variation was found for both patients and parents, ranging from virtually unaffected to severely affected. Normal sexual function and setting up a family were mentioned by patients and parents as being particularly important for quality of life. Over half (58%) of the patients had problems with sexual maturation and functioning, and continuous monitoring of all patients with thalassaemia intermedia by a paediatric endocrinologist is therefore strongly indicated. Most parents said, in light of their experiences, that they would opt for prenatal diagnosis and termination of affected pregnancies even if a genotype predicting the mild form of disorder were discovered.